Stunting Prevention Strategy With The Spider Risk Method - Nilawati, Iin; Herlinda, Herlinda; Lasmadasari, Novi (Jurnal MIDPRO, 2023)
Stunting being one _ focus problem crucial health in Indonesia. The prevalence of stunting is increasing from 35.6% in 2007 to 37.2 % in 2013 , and decreased to 27.7 % in 2019. Although occur decline , in Indonesia the disparity width in the province and decline the average still slow , while the target of decline to 14% in 2024. The stunting rate in Bengkulu Province is still enough high . Stunting has a huge impact for development quality source power human . Destination period long from study this for role as well as lower stunting through effort stunting prevention with Spider Risk. Stages study effectiveness spider risk method against effort Stunting Prevention begins of the bride and groom , ministry mother pregnant , sure labor facilitated service health , sure baby exclusive breastfeeding , monitoring _ fell continuous in 1000 HPK. Method research used _ is cross sectional with approach retrospective . Instruments used _ is google forms. Sample is 30 mothers who have child stunting risk in Bengkulu. Research results show that characteristics respondent majority have child manifold sex man male 63.3%, high school education 43%, working as mother house household 70%, income not enough from 1 million 40%, no risk of KEK 70%, age moment marry not enough from 20 years 46%, history of exclusive breastfeeding 66.7%, knowledge not enough about stunting there is 60%, distance pregnancy not enough from 2 years 30%, birth weight not enough from 2500 grams 20%, the risk of stunting is 36.7%. Based on analysis test results bivariate with using chi square is obtained results that that be factor risk or relate with stunting is _ variable whose P value is â‰¤ 0.05 , namely education mother , income family , KEK age marry not enough from 20 years , history of exclusive breastfeeding , knowledge mother and history heavy baby born not enough from 2500 grams.